2020
DOI: 10.1021/acs.iecr.0c03319
|View full text |Cite
|
Sign up to set email alerts
|

Separation Characteristics in a Novel Gas–Liquid Vortex Separator

Abstract: Fischer–Tropsch (FT) synthesis is an essential way to achieve the cleanliness of oil products. A novel gas–liquid vortex separator (GLVS) was put forward to use in the FT synthesis. GLVS has four symmetry vortex arms set inside the separator body. The characteristics of pressure drop and separation efficiency of the GLVS were investigated through a large-scale cold model. The influences of the inlet gas velocity and the inlet liquid concentration on the separator were analyzed. An improved weighting method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…30 Other researchers have proposed structural innovations in cyclone separators. 11,31,32 It can be seen from the literature review that the cyclone separator is a commonly used primary separation structure in the industry and has been widely concerned by researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Other researchers have proposed structural innovations in cyclone separators. 11,31,32 It can be seen from the literature review that the cyclone separator is a commonly used primary separation structure in the industry and has been widely concerned by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…When it is applied to the compressor system, the cyclone separator is often used. , Some researchers have studied the effect of the structural parameters of the cyclone separator, including the height of cyclone, , the length and diameter of the inner cylinder, the number and angle of inlet pipes, , and the surface roughness parameters . Other researchers have proposed structural innovations in cyclone separators. ,, It can be seen from the literature review that the cyclone separator is a commonly used primary separation structure in the industry and has been widely concerned by researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The spiral structure was used to generate centrifugal force to separate gas and liquid, which solved the blockage and segmented plugging flow phenomenon in the process of oil and gas gathering and transportation (Rosa et al, 2001). Zhou et al (2020) proposed a new gas-liquid vortex separator (GLVS), which symmetrically arranged multiple swirl arms within the separator. Dries and Hoffmann, (2019) found that the vane mist eliminator was a highefficiency droplet separator because it was durable and had certain stain resistance, and the separation efficiency was still high at higher working pressures.…”
Section: Introductionmentioning
confidence: 99%